(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Education for Sustainable Development (ESD) is a significant force in equipping future professionals and leaders with sustainability competencies and thereby transforming societies. However, it is clear from the literature that Higher Education Institutions (HEIs) do not completely comprehend the idea behind this challenge. ESD has been implemented in different ways and most of the Higher Education Institutions (though a lot of efforts have been done in this sector in the last decade) do not have a clear cut strategy for education for sustainability. In this paper we suggest a good starting point for the implementation and evaluation of ESD in HEIs. Due to the interconnectedness of different practices, presence of multiple stakeholders and the multi dimensionality of the concept, the ESD model for HEIs require a design with theoretical inspirations from different schools of thought. This article discusses the outcome based theoretical approach to ESD and develops an integrated, holistic and inclusive model – Transformative Human Development Model- for the realization of ESD in HEIs.